Faktor – Faktor Yang Mempengaruhi Impulsive Buying Pada Pengguna E-Commerce Di Indonesia - Florentina Ajeng Tiya Pratiwi; Dody Hapsoro; Wisnu Prajogo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to examine the effect of shopping enjoyment, hedonic shopping motivation, and price discounts on impulsive buying tendency, and impulsive buying tendency on impulsive buying behavior with self-control as a moderating variable. The sampling technique was carried out using a purposive sampling method. The questionnaire was distributed online using google form. Respondents who filled out a valid questionnaire were 190 respondents of e-commerce users to continue data processing. Researchers used two testing applications, namely SPSS version 28 and Warp PLS version 08. The results showed that H1 shopping enjoyment has a negative effect on impulsive buying tendency, H2 hedonic shopping motivation has a positive effect on impulsive buying tendency, H3 price discount has a positive effect on impulsive buying tendency, H4 impulsive buying tendency has a positive effect on impulsive buying behavior, and H5 self-control does not moderate the effect of impulsive buying tendency on impulsive buying behavior.